Gambaran Pengetahuan Mahasiswa mengenai Keselamatan, Kesehatan Kerja dan Lingkungan dengan Menggunakan Buku Panduan Digital K3L - Aprilya, Nurina; Puspitasari, Nilam; Abdul Rauf, Muhammad (Jurnal Kesehatan Pertiwi, 2024)
Introduction: Occupational Health, Safety, and Environment (OHSE) is an important aspect in the industrial and educational sectors, especially for students as future professionals. This study aims to evaluate the level of students' knowledge regarding OHSE after being educated through a digital guidebook. Research Objectives: To describe students' knowledge about occupational health, safety, and environment using the OHSE guidebook. Research Methods: This research was conducted from September to November 2024. This type of research is descriptive, with a population of 50 students from the Health Promotion Study Program at Jember State Polytechnic, using purposive random sampling technique. The measurement tool used was a questionnaire. Results of the study: The study shows that before the education was provided, 46% of students had poor knowledge, 34% had sufficient knowledge, and 20% had good knowledge. After the education, the percentage of students with good knowledge increased to 72%, while those with poor knowledge decreased to 12%. These findings indicate that the digital OHSE guidebook is effective in enhancing students' knowledge about occupational health, safety, and environment. Conclusion: This increase in knowledge is expected to foster more compliant behavior towards OHSE procedures, thereby creating a safer environment on campus and in the workplace. This research provides important insights for the development of OHSE curriculum and training programs in higher education institutions.